2005
DOI: 10.1159/000089967
|View full text |Cite
|
Sign up to set email alerts
|

Intermuscular Interaction between Synergists in Rat Originates from both Intermuscular and Extramuscular Myofascial Force Transmission

Abstract: The purpose of the present study is to investigate the origin of mechanical interactions between the rat extensor digitorum longus (EDL) muscle and the grouped tibialis anterior and extensor hallucis longus muscles (TA+EHL). The proximal and distal tendons of EDL as well as the tied distal tendons of TA+EHL were transected and connected to force transducers. Connective tissues at the muscle bellies of the anterior crural compartment were left intact. Supramaximal stimulation of the common peroneal nerve activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 42 publications
0
42
0
1
Order By: Relevance
“…This suggests there is some transmission of force to adjacent structures, presumably by extramuscular connective tissue (Maas et al, 2005). The presence of inter-muscular myofascial force transmission would violate the assumption, made in our analysis, that passive tension in the gastrocnemius depends only on the knee and ankle angles.…”
Section: Discussionmentioning
confidence: 51%
“…This suggests there is some transmission of force to adjacent structures, presumably by extramuscular connective tissue (Maas et al, 2005). The presence of inter-muscular myofascial force transmission would violate the assumption, made in our analysis, that passive tension in the gastrocnemius depends only on the knee and ankle angles.…”
Section: Discussionmentioning
confidence: 51%
“…Therefore, only one EDL muscle compartment was most likely excited. Because EDL muscle belly is accessible only after a full longitudinal fasciotomy of the anterior crural compartment Maas et al, 2005), this was performed after the first set of measurements (see experimental protocol below).…”
Section: Surgerymentioning
confidence: 99%
“…Myofascial connections between a muscle's epimysium and surrounding structures can also transmit force (Huijing, 2009;Maas and Sandercock, 2010). Several studies, in which muscles within the rat anterior crural compartment were excited maximally and their tendons were severed from the skeleton, have shown that forces exerted at the tendon of a muscle kept at a constant muscletendon unit (MTU) length were dependent on the neighboring muscle's length (Huijing and Baan, 2008;Huijing et al, 2007;Maas et al, 2005;Meijer et al, 2006;Rijkelijkhuizen et al, 2007) or relative position (Maas et al, 2004). However, several of these imposed changes were beyond those found during normal movement.…”
Section: Introductionmentioning
confidence: 99%
“…Force can also be transmitted via intermuscular and extramuscular connective tissues (29), termed epimuscular myofascial force transmission. Mechanical interaction between muscles is an effect of such force transmission, which is defined as a change in force of restrained muscles caused by changes in MTU length of an adjacent muscle (28). The degree of force transmission between muscles depends on the force-transmitting ability of the myofascial pathways.…”
mentioning
confidence: 99%